Pengaruh Pendekatan Sosio-Saintifik Isu terhadap Kemampuan Berpikir Kritis Siswa - Siti Ainun Jariah; Tien Aminatun (Postgraduate, University of Mataram, 2022)
This study aims to determine the effect of the socio-scientific issue approach with the investigative group learning model on the critical thinking skills on environmental change. This study uses a quasi-experimental method with a pretest-posttest control group design. The research population is the students of class X IPA SMAN 1 Batu Sopang, Paser Regency, East Kalimantan, in the academic year 2020/2021. The samples were class X IPA 1 (experimental group) and X IPA 2 (control group) . The test instrument used is a written test. The average pre-test and post-test of the experimental class increased by 15.86, while the average value of the pre-test and post-test of the control class increased by 8.62. the two classes have a difference of 7.24. The N-Gain test result for the experimental class is 0.33, including the medium category and the control class is 0.20, including the low category. The results of the independent samples t-test are sig. 0.08 < 0.05 and t count 2.740 > 1.99, meaning that H0 is rejected. Based on the study results, the socio-scientific approach to issues with the investigative group learning model proved to be more effective in improving students' critical thinking skills than conventional learning models